2009
DOI: 10.1186/1748-5908-4-78
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing evidence-based practice: an organizational case study using a model of strategic change

Abstract: BackgroundThere is a general expectation within healthcare that organizations should use evidence-based practice (EBP) as an approach to improving the quality of care. However, challenges exist regarding how to make EBP a reality, particularly at an organizational level and as a routine, sustained aspect of professional practice.MethodsA mixed method explanatory case study was conducted to study context; i.e., in terms of the presence or absence of multiple, inter-related contextual elements and associated str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 39 publications
6
129
1
6
Order By: Relevance
“…44 distributed leadership has been shown to provide a necessary condition and mechanism for collective action around implementation. 16,113 It has been suggested that leadership within collaboration is concerned with making things happen -specifically, the formulation of the collaboration's plan/policy and activity agenda. 76 The importance of leadership for successful change, innovation and implementation is reflected in existing theory and frameworks (e.g.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 distributed leadership has been shown to provide a necessary condition and mechanism for collective action around implementation. 16,113 It has been suggested that leadership within collaboration is concerned with making things happen -specifically, the formulation of the collaboration's plan/policy and activity agenda. 76 The importance of leadership for successful change, innovation and implementation is reflected in existing theory and frameworks (e.g.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Although there are some exceptions to this (e.g. Dopson and Fitzgerald, 111 Crammer et al, 112 Stetler et al 113 ), we know little about how and/or why implementation might take place within more sustained interactions such as organisational partnerships and collaborations like CLAHRCs. While reinforcing some aspects of the existing evidence base, such as that implementation is multifaceted and context is important, our findings also provide a more detailed narrative about the nature and pattern of interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Nine of the 17 studies provided information that allowed assessment of how leadership was operationalized (Aarons, 2006, Boström et al, 2007, Brown and McCormack, 2011, Cummings et al, 2010, Estabrooks et al, 2007, Forsman et al, 2012, Hagedorn and Heideman, 2010, Schultz and Kitson, 2010, Stetler et al, 2009). The studies varied greatly with respect to how leadership was measured and how instruments were used.…”
Section: Operationalization Of Leadershipmentioning
confidence: 99%
“…[89][90][91] Our findings help to explain that context does not simply act as a backdrop to action (i.e. as a set of obstacles or facilitators), but that is where implementation takes place.…”
Section: Contextmentioning
confidence: 99%